Neuroprotective Effect of Resveratrol via Activation of Sirt1 Signaling in a Rat Model of Combined Diabetes and Alzheimer’s Disease - Ma, XingRong; Sun, ZhiKun; Han, Xiao; Li, Shujian; Jiang, Xiaofeng; Chen, Shuai; Zhang, Jiewen; Lu, Hong (Frontiers in Neuroscience, 2020)
Backgound: Alzheimer’s disease (AD) and diabetes mellitus (DM) often co-exist in patients because having one of these conditions increases risk for the other. These two diseases share several pathophysiological mechanisms, such as specific inflammatory signaling pathways, oxidative stress, and cell apoptosis. It is still unclear exactly which mechanisms associated with DM are responsible for increased AD risk. Studies have found that even transient elevation of brain Aβ levels can allow T2DM to slightly disrupt the neural milieu in a way that encourages pathologies associated with the onset of memory deficits and AD. A recent study argues that a potential common pathogenetic mechanism underlying both DM and AD is evidenced by the cooccurrence of amyloid brain legions and deposits containing both tau and Aβ in pancreatic β cells. Given these links, an investigation detailing disease mechanisms as well as treatment options for patients with cooccurring DM and AD is urgently needed. The biological effects of resveratrol relevant to DM and AD treatment include its abilities to modulate oxidative stress and reduce inflammation. A rat model of diabetes mellitus and concomitant Alzheimer's disease was created for this study using intraperitoneal injection of streptozotocin and hippocampal injection of Aβ1-40 in order to characterize resveratrol’s potential protective action. Results: Resveratrol siginificantly inhibited memory impairment, increased acetylcholinesterase (AchE) and malondialdehyde (MDA) levels as well as Sirt1 expression, and decreased levels of choline acetyltransferase (ChAT), superoxide dismutase (SOD), glutathione (GSH), IL-1β, and IL-6 in this rat model of diabetes and concomitant Alzheimer's disease. The sirt1 inhibitor EX527 partially reversed the effects of resveratrol. Conclusion: This study suggests that resveratrol may have a neuroprotective action through activation of Sirt1 signaling in diabetes and Alzheimer's disease with concurrent onset.